2018
DOI: 10.1111/jace.16094
|View full text |Cite
|
Sign up to set email alerts
|

Structure variation and energy storage properties of acceptor‐modified PBLZST antiferroelectric ceramics

Abstract: Energy storage capacitors with high recoverable energy density and efficiency are greatly desired in pulse power system. In this study, the energy density and efficiency were enhanced in Mn‐modified (Pb0.93Ba0.04La0.02)(Zr0.65Sn0.3Ti0.05)O3 antiferroelectric ceramics via a conventional solid‐state reaction process. The improvement was attributed to the change in the antiferroelectric‐to‐ferroelectric phase transition electric field (EF) and the ferroelectric‐to‐antiferroelectric phase transition electric field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“… 3 , 126 Furthermore, doping with Ba and Sr (A-site) improves fatigue behavior and temperature stability, suppresses the stress sensitivity, and enhances energy storage. 148 , 150 153 , 155 , 161 , 173…”
Section: State-of-the-art In Electroceramics For Energy Storagementioning
confidence: 99%
See 1 more Smart Citation
“… 3 , 126 Furthermore, doping with Ba and Sr (A-site) improves fatigue behavior and temperature stability, suppresses the stress sensitivity, and enhances energy storage. 148 , 150 153 , 155 , 161 , 173…”
Section: State-of-the-art In Electroceramics For Energy Storagementioning
confidence: 99%
“…To further optimize the energy storage properties of PLZT ceramics, Sn may be substituted on the B-site of PLZT, which broadens the AFE compositional range, ,,,,, in accordance with phase diagram from 1989 (Figure ). (Pb 0.97 La 0.02 )­(Zr,Sn,Ti)­O 3 with 2 mol % La has been most commonly studied in which the Zr/Ti/Sn ratio is varied to give a complex phase diagram that contains FE tetragonal (F T ), high-temperature nontilted FE rhombohedral (F R(HT) ), low temperature FE rhombohedral (F R(LT) ) AFE tetragonal (A T ), and AFE orthorhombic (A O ) phases.…”
Section: State-of-the-art In Electroceramics For Energy Storagementioning
confidence: 99%
“…In the range of wavenumbers of <100 cm À1 , the peak width broadened obviously with increasing Sr 2+ content, which is mainly ascribed to the chemical cation disorder. 35 In addition, the peaks exhibit a tiny shi with the increase of Sr 2+ content, which can be conrmed from the peaks at 125, 250 and 280 cm À1 , indicating the entrance of ionic Sr 2+ into the lattice. 45 These phenomena are in good agreement with previous studies, demonstrating that Sr 2+ doping is likely to disorder the local structure and disperse the phase transition between AFE and FE.…”
Section: Resultsmentioning
confidence: 95%
“…For instance, Liu et al found that the AFE-FE phase transition (E F ) and AFE-FE phase transition eld (E A ) of Mn-doped (Pb 0.87 Ba 0.1 La 0.02 ) (Zr 0.65 Sn 0.3 Ti 0.05 )O 3 ceramics increased from 11.9 to 12.8 kV mm À1 and from 7.6 to 9.3 kV mm À1 , respectively, realizing a W rec of 2.64 J cm À3 . 35 Similarly, Sr was introduced to the A-site of (Pb 0.97 La 0.02 )(Zr 0.75 Sn 0.195 -Ti 0.055 )O 3 , which exhibited a high W rec of 5.56 J cm À3 due to the strengthened E F and E A . 36 On the other hand, breakdown strength (BDS) also plays a pivotal role in increasing energy density.…”
Section: Introductionmentioning
confidence: 99%
“…19 Some natural templates have been used to design NiO-based porous nanostructures such as nanocrystalline cellulose, 20 eggshell membrane, 21 lotus pollen grains, 22 guar gum, 23 starch, 24 and pinewood. 25 However, to the best of our knowledge, there have seldom been reports of using natural KGM as a sacricial support for designing highly porous NiO nanostructures in today's literature. Here, we report a novel synthetic route to 3D NiO nanostructures using biotemplating KGM nanobrils and their gas sensing characteristics were systematically investigated.…”
Section: Introductionmentioning
confidence: 99%